A Systematic Review of Instruments to Assess Guilt in Children and Adolescents - Zaccari, Vittoria; Aceto, Marianna; Mancini, Francesco (Frontiers in Psychiatry, 2020)
Background: Guilt feelings have received considerable attention in past psychological theory and research. Several studies have been conducted that represent a range of views and propose various implications of guilt in children and adolescents. Variations in theoretical definitions of guilt, emphasizing a lack of measurement convergence, make it difficult to derive a comprehensive definition of the construct in childhood and adolescence. Research shows substantial variability in instruments used to measure guilt in children and adolescents. Purpose: The aim is to discuss existing contributions, illustrating the empirical validity of the available instruments used to measure guilt and identifying the nature of their theoretical backgrounds among children and adolescents. Methods: A systematic search was conducted using the following databases: PsycINFO, PsycARTICLES, MEDLINE, Scopus, Web of Science, and PubMed (all years up to February 19, 2020). Search terms were compiled into three concepts for all databases: “measure,” “guilt,” and “childhood/adolescence.” In addition, a search was conducted to detect the gray literature. Results: After removing the duplicates, a total of 1,408 records were screened, resulting in the identification of 166 full-text articles to be further scrutinized. Upon closer examination, there was consensus that 148 of those studies met the study inclusion criteria or were not retrieved. Twenty-five studies were included in the quality assessment. The data were organized on three main categories: (1) interpersonal or prosocial guilt; (2) intrapunitive guilt or that referring to an excessive sense of responsibility; 3) not specifying a theoretical construct. A great heterogeneity in psychometric evaluations and substantial variability in guilt construct emerged. The construct most represented and supported by valid instruments was interpersonal or prosocial guilt. Analysis of the gray literature showed that some instruments were not immediately available to the clinical and scientific communities. Conclusions: The studies analyzed and selected for qualitative review employed various instruments to measure guilt. Results confirmed what is widely documented in the literature about substantial variability in instruments used to measure guilt. We argue the need to develop measures that assess currently overlooked dimensions of guilt and to provide further additional information about the psychometric proprieties of the available developed instruments.